Repositioning Salirasib as a new antimalarial agent. Issue 9 (17th July 2019) - Porta, Exequiel O. J.; Bofill Verdaguer, Ignasi; Perez, Consuelo; Banchio, Claudia; Ferreira de Azevedo, Mauro; Katzin, Alejandro M.; Labadie, Guillermo R.
Abstract : Repurposing strategies present an enormous advantage for drug discovery, especially in malaria, where resources are scarce. Abstract : Malaria is a serious tropical disease that kills thousands of people every year, mainly in Africa, due to Plasmodium falciparum infections. Salirasib is a promising cancer drug candidate that interferes with the post-translational modification of Ras. This S -farnesyl thiosalicylate inhibits isoprenylcysteine carboxyl methyltransferase (ICMT), a validated target for cancer drug development. There is a high homology between the human and the parasite enzyme isoforms, in addition to being a druggable target. Looking to repurpose its structure as an antimalarial drug, a collection of S -substituted derivatives of thiosalicylic acid were prepared by introducing 1, 2, 3-triazole as a diversity entry point or by direct alkylation of the thiol. We further investigated the in vitro toxicity of FTS analogues to Plasmodium falciparum in the asexual stages and in Vero cells. An antiplasmodial activity assay was performed using a simple, high-sensitivity methodology based on nanoluciferase (NLuc)-transfected P. falciparum parasites. The results showed that some of the analogs were active at low micromolar concentration, including Salirasib. The most potent member of the series has S -farnesyl and the 1, 2, 3-triazole moiety substituted with phytyl. However, the compound substituted with methyl-naphthyl shows promising physicochemical and activity values. The low cytotoxicity in eukaryotic cells of the most active analogs provided good therapeutic indices, being starting-point candidates for future antimalarial drug development.